1972
DOI: 10.1136/bmj.4.5839.550-b
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol infusions and lithium excretion.

Abstract: thyroxine 0.1 uig/100 ml, total fats 1,820 mg/100 ml, cholesterol 523 mg/100 ml, urea 516 mg/100 ml, creatinine 6.6 mg/100 ml, and uric acid 17 mg/100 ml. The glomerular filtration rate measured by creatinine clearance was 7 ml/min. The bladder was drained by an indwelling catheter and the patient was given triiodothyronine. After 10 days she recovered bladder control, the urea was 80 mg/ 100 ml, and the creatinine clearance 25 ml/min. The electroencephalogram became normal. After four months the urea was 42 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Lithium excretion has been hastened by the use of urea, which acts as an osmotic diuretic 4 but Mannitol has not been previously used in man. Obek 5 however showed that it increased lithium excretion in dogs. Alkaline diuresis in the form of added sodium bicarbonate 4 and M/6 Lactate 6 also appears to speed renal lithium excretion.…”
Section: Discussionmentioning
confidence: 97%
“…Lithium excretion has been hastened by the use of urea, which acts as an osmotic diuretic 4 but Mannitol has not been previously used in man. Obek 5 however showed that it increased lithium excretion in dogs. Alkaline diuresis in the form of added sodium bicarbonate 4 and M/6 Lactate 6 also appears to speed renal lithium excretion.…”
Section: Discussionmentioning
confidence: 97%